Penerapan Metode Pembelajaran Kreatif dalam Mengembangkan Kemampuan Problem Solving Pada Anak Usia Dini - Jusni; Muhammad Suyuthy R. (Jurnal Euforia, 2026)
This study aims to describe the implementation of creative learning methods in developing problem-solving skills among early childhood learners at TK Tellung Poccoe YAPIT Taretta, Amali District, Bone Regency. This research employed a qualitative field research approach. The participants consisted of the principal, teachers, and children. Data were collected through observation, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña interactive model. The findings revealed that: (1) the implementation of the creative learning model at TK Tellung Poccoe YAPIT Taretta, Amali District, Bone Regency was carried out by providing children with opportunities to express themselves freely, develop their imagination, and generate new ideas through meaningful play-based activities. Teachers employed various creative instructional strategies, including role-playing, storytelling, singing, drawing, dancing, and simple science experiments; (2) following the implementation of the creative learning model, the children's problem-solving skills improved, as reflected in their ability to identify problems, generate ideas, collaborate with peers, test and evaluate alternative solutions, and demonstrate more positive attitudes during the learning process; and . (3) the challenges encountered by teachers in implementing the creative learning model to foster problem-solving skills included: (a) limited learning facilities and infrastructure; (b) differences in children's characteristics and developmental abilities; (c) limited instructional time allocated for kindergarten learning activities; (d) insufficient parental support, as many parents remained primarily focused on early academic skills, particularly reading, writing, and arithmetic; and (e) limited teacher competence in designing and implementing creative learning activities.